How Schools Can Help Students Recover from Traumatic Experiences - Jaycox, Lisa H. (RAND Corporation, 2006)
This tool kit describes how trauma exposure impacts students' performance and behavior and provides a compendium of programs for schools to support the long-term recovery of traumatized students. It also compares the programs with one another.